PELATIHAN PENYUSUNAN DAN PELAPORAN SPT TAHUNAN PADA UMKM DI KECAMATAN TOBELO - Sinen, Kasim; Malik , Mahardika Catur Putriwana; Kusumaningrum , Sheila; Santoso, Septy Indra (Inspirasi: Jurnal Pengabdian Masyarakat, 2024)
The purpose of this Community Service (PKM) activity is to provide an understanding to MSMEs about their tax obligations, namely accounting, depositing, and reporting taxes. This PKM activity was carried out in September 2024, this PKM was attended by the local government and MSME actors who were fostered by the PKM Partner, namely the Tobelo Cooperative and MSME Service. The method used in this PKM activity is the socialization method, where this socialization method includes education and counseling as a means of transferring knowledge and education in the form of lectures, tutorials and discussions. The material provided includes tax regulations, understanding of tax income and other tax obligations, as well as training in reporting Annual Tax Returns for MSMEs. The results obtained from this PKM activity are to make MSMEs more aware of their tax obligations which are not only calculating and depositing but also reporting as part of taxpayer compliance.